2001
DOI: 10.2307/2679962
|View full text |Cite
|
Sign up to set email alerts
|

Life-History Variation, Phenotypic Plasticity, and Subpopulation Structure in a Freshwater Snail

Abstract: Earlier studies of habitat-specific subpopulations of mixed clonal and sexual freshwater snails of the species Potamopyrgus antipodarum have revealed clinal variation by depth in several life-history traits, risk of parasite infection, mixed population structure, and the genetic structure of the clonal population. Clinal variation is pronounced in lifehistory traits: snails are larger and start reproduction later in the deeper habitats. The proportion of clonal individuals increases with depth, and many clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…We would agree that the possibility exists that there are microhabitats within each of these areas, upon which the many different clones might specialize, but the existence of these microhabitats is not obvious to us at the present time. Soft selection might, however, play some role in the distribution of clones among habitats in both Lakes Alexandrina and Tennyson, but recent reciprocal transplant experiments have suggested that clones may be quite plastic with respect to habitat use (Negovetic & Jokela, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We would agree that the possibility exists that there are microhabitats within each of these areas, upon which the many different clones might specialize, but the existence of these microhabitats is not obvious to us at the present time. Soft selection might, however, play some role in the distribution of clones among habitats in both Lakes Alexandrina and Tennyson, but recent reciprocal transplant experiments have suggested that clones may be quite plastic with respect to habitat use (Negovetic & Jokela, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…; Dybdahl and Drown ). In the native range of P. antipodarum , variation in shell morphology reflects adaptive responses to abiotic and biotic factors (Negovetic and Jokela ; Haase ; Holomuzki and Biggs ). However, little is known about how variation in shell morphology affects the success of invasive populations across broad environmental gradients.…”
Section: Methodsmentioning
confidence: 99%
“…A single clonal genotype, US 1, has spread rapidly in the western United States since 1987, and sometimes reaches great abundance (Hall et al 2003(Hall et al , 2006Kerans et al 2005;Dybdahl and Drown 2011). In the native range of P. antipodarum, variation in shell morphology reflects adaptive responses to abiotic and biotic factors (Negovetic and Jokela 2001;Haase 2003;Holomuzki and Biggs 2006). However, little is known about how variation in shell morphology affects the success of invasive populations across broad environmental gradients.…”
Section: Study Systemmentioning
confidence: 99%
“…Native P. antipodarum are intermediate hosts for at least 14 species of endoparasites including castrating trematodes (Hechinger, ; Winterbourn, ). Infection of juvenile P. antipodarum by parasites, and in particular castrating trematodes, may affect shell morphology and brood size through changes in resource allocation of the growing snail (Levri, Dillard, & Martin, ; Negovetic & Jokela, ). For example, infected P. antipodarum are wider and less spiny than uninfected counterparts (Lagrue, McEwan, Poulin, & Keeney, ; Levri et al., ).…”
Section: Introductionmentioning
confidence: 99%